2002
DOI: 10.1016/s0042-6989(01)00185-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiology and privilege of neuronal retina and pigment epithelium transplants

Abstract: Despite the existence of ocular immune privilege, immune rejection may be a barrier to successful retinal transplantation. We have examined in mice the extent to which the subretinal space (SRS) is an immune privileged site, and whether retinal pigment epithelium and neuronal retinal tissue have properties of immune privileged tissues. We report that (1) The SRS is an immune privileged site; (2) Neonatal RPE is an immune privileged tissue; (3) Neuronal retina is a partially immune privileged tissue; and (4) Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
115
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(119 citation statements)
references
References 13 publications
1
115
0
3
Order By: Relevance
“…Placement of allogeneic tissue into the anterior chamber of the eye results in a protective response called anterior chamber-associated immune deviation (ACAID). 33 Similar immune deviation could be occurring in retinal implant recipients, which could explain graft survival despite the presence of HLA-mismatched graft antigens. If regulatory T cells are developing in response to retinal implants, they are not inhibiting memory B-cell antibody production as all antibody specificities, donor directed and non-donor specific, persisted in all sensitized patients studied here.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Placement of allogeneic tissue into the anterior chamber of the eye results in a protective response called anterior chamber-associated immune deviation (ACAID). 33 Similar immune deviation could be occurring in retinal implant recipients, which could explain graft survival despite the presence of HLA-mismatched graft antigens. If regulatory T cells are developing in response to retinal implants, they are not inhibiting memory B-cell antibody production as all antibody specificities, donor directed and non-donor specific, persisted in all sensitized patients studied here.…”
mentioning
confidence: 96%
“…33 Lack of apparent cell-mediated rejection of the retinal tissue implanted to the subretinal space likely derives from this immunologic protection. 33 Additionally, the absence of detectable graft damage from donor-specific antibodies that were present in some patients before implantation would indicate that the blood-brain barrier is prohibiting antibody infiltration into the subretinal space. Placement of allogeneic tissue into the anterior chamber of the eye results in a protective response called anterior chamber-associated immune deviation (ACAID).…”
mentioning
confidence: 99%
“…Previous studies have shown that the retinal pigment epithelium (RPE) 4 monolayer functions as an immune-privileged tissue (4), and that RPE cells are the principal mediators of immune privilege in the subretinal space (5,6). Ocular pigment epithelium cells, either as explanted tissues or cultured cells, have been found to be immunosuppressive in vitro (7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…It may suggest a more ''fitting niche'' of that region for tumor growth, or expression of certain chemoattractants as well as adhesion molecules and/or chemokines in that region, or protection from host immune responses. Indeed, the SRS in the retina has been shown a ''immunoprivileged site'' for tumors or allogeneic transplants (34). We intend to investigate the mechanism(s) of this phenomenon and this mouse model seems very applicable.…”
Section: Discussionmentioning
confidence: 99%